(E)-N-[(E)-3-(4-Nitrophenyl)allylidene]naphthalen-1-amine - Nam, K.D.; Cha, J.H.; Cho, Y.S.; Lee, J.K.; Pae, A.N. (2013)
In the title compound, C19H14N2O 2, the dihedral angle between the mean planes of the 4-nitrophenyl ring and the naphthalene ring system is 12.79 (2)°. The imine group displays a C-C-N=C torsion angle of 41.0 (2)° and the C=N group has an E conformation. In the crystal, weak C-H？O hydrogen bonds link molecules into layers parallel to the b axis.